L-arginine prevents hypoxia-induced vasoconstriction in dual-perfused human placental cotyledons. Issue 11 (November 2015) - Bednov, Andrey; Espinoza, Jimmy; Betancourt, Ancizar; Vedernikov, Yuri; Belfort, Michael; Yallampalli, Chandrasekhar
Abstract: Introduction: Chronic hypoxia in the uteroplacental unit is associated with increased resistance to blood flow in the fetal-placental circulation. These changes can lead to adverse cardiovascular events in adulthood. This study investigates whetherl -arginine (substrate for nitric oxide synthase (NOS) or endothelin-A receptor antagonist BQ123 administration reverses hypoxia-induced changes in perfusion pressure in the fetal compartment in dual-perfused placental cotyledons. Methods: Human placental cotyledons (n = 15) from term deliveries (n = 15) were perfused with Krebs solution from maternal and fetal sides. Normal and reduced oxygen tension conditions were sequentially created in the perfused maternal compartment. Fetal perfusion pressure was continuously monitored. 1 mMl -arginine, d -arginine (an enantiomer ofl -arginine and not a substrate for NOS), and BQ123 or normal saline were administered to the fetal compartment;l -arginine was also administered to the maternal compartment prior to maternal side hypoxia. Changes in perfusion pressure were compared between groups. Results: Maternal hypoxia increased (19 ± 6%) perfusion pressure and this was blunted byl -arginine injection (3 ± 5%; p = 0.006) into the fetal compartment.l -arginine in the maternal compartment had no significant effect (22 ± 4% withl -arginine vs.14 ± 3% at control) on perfusion pressure. Similarly, d -arginine (23 ± 11% vs.19 ± 8% at control) or BQ123 (12 ± 3% vs.13 ± 3% at control) in the fetal compartment did not blunt the hypoxia-induced increase in perfusion pressure. Conclusions: Fetal vasoconstriction induced by maternal hypoxia is blunted by NO synthase substratel -arginine, but not byd -arginine, in the fetal compartment, suggesting the involvement of NO synthesis in regulating the hypoxia-induced fetal vasoconstriction. Endothelin A receptor-related mechanisms does not appear to play a role in the maternal hypoxia-induced fetal vasoconstriction. Highlights: We studied fetal vascular reactivity of perfused human placenta ex vivo. Maternal hypoxia increases the fetal perfusion pressure. l -arginine infused into fetal compartment blunts perfusion pressure raise. Fetald -arginine and BQ123 do not blunt hypoxia-induced vasoconstriction.